Fabrication of silicon embedded isomeric chalcone linkers using [CuBr(PPh3)3]. (29th March 2017) - Singh, Gurjaspreet; Singh, Jasbhinder; Kaur, Gurpreet; Singh, Jandeep
Graphical abstract: The positional isomeric units of substituted chalcones were synthesized using [CuBr(PPh3 )3 ] as source of catalyst. Abstract: The positional isomeric units of substituted chalcones were synthesized using [CuBr(PPh3 )3 ] as source of catalyst. The alkynes (1a–9a ) were fabricated with azides resulting into triazole moiety containing triethoxysilane substituents (1b–9b ) which were further converted into silatranes1c–9c . The synthesized compounds were confirmed by spectroscopic analytical studies like NMR (1H, 13C), IR, mass recognition studies confirm the silatrane product formation.